LIPID AUTOXIDATION OF FISH, LARD, CORN AND LINSEED OILS BY ISOTHERMAL CALORIMETRY - HAMAN, N.; BODNER, M.; FERRENTINO, G.; SCAMPICCHIO, M. (Italian Journal of Food Science, 2018)
This work proposes an approach to characterize lipid oxidation of oils based on the measurement of isothermal calorimetry data, including information on the duration of the monomolecular, bimolecular and termination periods. The approach has been exploited with fish and lard oil samples at temperatures from 40 to 80°C and with corn and linseed oils at 80°C. The length of the monomolecular period was the most sensitive to the variation of temperature. Accordingly, the monomolecular period was used as index of oxidative stability of oils. Thus, the highest oxidative stability was observed for corn oil samples at 80°C (tmono = 2060 min), followed by linseed (tmono = 390 min), fish (tmono = 40 min) and lard oils (tmono = 30 min). The different stability of the samples was discussed with their fatty acids profile and antioxidant activity. The results confirmed that the content in natural antioxidants is the key responsible for the final oxidative stability of the samples.